Pelaksanaan Autonomi di Daerah Provinsi Riau dan Impaknya ke atas Pembangunan Masyarakat - Muhammad Iqbal (2011)
The purpose of the thesis is, firstly, to identify the implementation of regional autonomy, secondly, to identify the already autonomous areas, and thirdly, to assess its impact on societal development. The study was conducted at three selected regions, namely, Kota Pekanbaru, Kabupaten Indragiri Hulu and Kabupaten Indragiri Hilir. Research study indicated that the implementation of regional autonomy exercised by the government/administration at these three regions, is ineffective. Nevertheless, consensus on development plan (musrenbang) through the district-level working union (SKPD) on its implementation has not been in tandem with the government policy as the concern is only with the local and central government. The awarding of district autonomy is categorized as not effective at the government of Kota Pekanbaru based on regional regulations (perda) number 23 (year 2004), Kabupaten Indragiri Hulu based on regional regulation number 103 (year 2005), and Kabupaten Indragiri Hilir based on regional regulation number 10 (year 2005). Additionally, effective implementation of societal development is categorized as ineffective on the development of basic facilities, infrastructure and also the many years of development. According to the Analytical System Theory, the analysis of result shows that the government of Kota Pekanbaru, Kabupaten Indragiri and Kabupaten Indragiri Hilir is categorized as ineffective in line with Law 32 (year 2004) on regional autonomy.